A Novel Integrated Cognitive-Behavioral Therapy for Anxiety and Medication Adherence Among Persons Living With HIV/AIDS. Issue 1 (February 2018) - Brandt, Charles P.; Paulus, Daniel J.; Garza, Monica; Lemaire, Chad; Norton, Peter J.; Zvolensky, Michael J.
Abstract: Persons living with HIV/AIDS (PLHIV) are able to live full lifespans after infection, however, rates of anxiety disorders among this population are elevated compared to national samples. Importantly, these anxiety symptoms and disorders have a negative effect on medication adherence, quality of life and other psychological disorders, such as depression. In order to reduce the impact of anxiety among PLHIV, a six-session transdiagnostic CBT-based treatment manual for anxiety among PLHIV named the HIV/Anxiety Management-Reduction Treatment (HAMRT) was developed and implemented. The current manuscript discusses the content of this manual as well as results from three cases examining the impact of HAMRT. Results indicated that HAMRT was effective in reducing symptoms of anxiety, anxiety sensitivity, depression, and negative affect among our sample. Additionally, results indicated that HAMRT was effective in increasing HIV medication adherence as well as quality of life. Results are discussed in terms of the potential utility of an anxiety-reduction therapy program aimed at increasing medication adherence among PLHIV. Highlights: A six-session CBT-based transdiagnostic anxiety treatment was administered to three persons living with HIV. Persons receiving treatment showed decreases in anxiety symptoms, anxiety sensitivity, depression symptoms, and negative affect. Persons receiving treatment showed increases in HIV medication adherence and quality of life.